2020
DOI: 10.1016/j.avsg.2020.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Venous Thromboembolism in COVID-19 Patients: A Multicenter Experience from Northern Italy

Abstract: Background The liability of patients affected by novel coronavirus disease (COVID-19) to develop venous thromboembolic events is widely acknowledged. However, many particulars of the interactions between the two diseases are still unknown. This study aims to outline the main characteristics of deep venous thrombosis (DVT) and pulmonary embolism (PE) in COVID-19 patients, based on the experience of four high-volume COVID-19 hospitals in Northern Italy. Methods All cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 8 publications
4
35
0
Order By: Relevance
“…After excluding duplicates and preliminary screening, 151 full-text articles were assessed for eligibility and 130 studies were excluded for not meeting the inclusion criteria, leaving 23 investigation fulfilling the inclusion criteria ( Fig. 1) [1,3,4,8,12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Search Results and Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…After excluding duplicates and preliminary screening, 151 full-text articles were assessed for eligibility and 130 studies were excluded for not meeting the inclusion criteria, leaving 23 investigation fulfilling the inclusion criteria ( Fig. 1) [1,3,4,8,12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Search Results and Included Studiesmentioning
confidence: 99%
“…Although the concomitant comorbidities were not systematically recorded by all investigations, active cancer and previous venous thromboembolic events were reported in a small percentage of cases. Fourteen studies considered ICU patients [1 , 3 , 4 , 8 , [16] , [17] , [18] , [19] , [20] , 22 , 25 , 26 , 28] while fifteen provided data of subjects hospitalized in general wards [1 , 8 , 17 , 20 , 21 , 23 , 24 , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] . Seven studies reported the data of both ICU and general wards patients [1 , 8 , 17 , 19 , 20 , 26 , 28] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study of 101 COVID-19 in-hospital patients undergoing duplex ultrasound (DUS) for clinically suspected DVT indicated that 42 were positive for DVT, 7 for superficial thrombophlebitis and 24 for PE, 8 of which associated with a DVT. 22 Time of onset varied greatly, but diagnosis was more frequent in the first 2 weeks since hospital admission (73.8%). Most PEs involved the most distal pulmonary vessels, and two thirds occurred in absence of a recognizable DVT, suggesting a primary thrombosis rather than embolism.…”
mentioning
confidence: 99%
“…Most PEs involved the most distal pulmonary vessels, and two thirds occurred in absence of a recognizable DVT, suggesting a primary thrombosis rather than embolism. 22 A single-center review of 214 CTPA studies in 1477 patients with suspected or confirmed COVID-19 indicated that the diagnostic yield for PE was 37%. 23 The overall proportion of PE in patients with COVID-19 was 5.4%.…”
mentioning
confidence: 99%